Advanced Cybersecurity Strategies for Protecting Critical Infrastructure: Strengthening the Backbone of National Security - Jahan Simu, Sumiya; Zaman, Fardin Ibn (International Journal of Scientific Research and Management (IJSRM), 2023)
In an era characterized by rapidly evolving cyber threats, the safeguarding of critical infrastructure (CI) has become paramount. Cyber threats are not only growing in sophistication but also in frequency, presenting unprecedented challenges to the security of essential systems. Critical infrastructure encompasses vital sectors such as energy, transportation, healthcare, and financial services, all of which serve as the backbone of modern societies. The interconnectedness of these infrastructures means that a disruption in one sector can lead to cascading effects across others. For instance, a cyberattack on a power grid can result in widespread outages, impacting hospitals, transportation systems,and financial institutions, thereby resulting in chaos and significant economic repercussions. Such disruptions pose serious risks to national security and public safety, as evidenced by incidents like the ransomware attack on the Irish Health Service Executive in 2021, which disrupted medical services and endangered lives.The increasing reliance on digital technologies, including the Internet of Things (IoT) and cloud computing, further complicates the cybersecurity landscape. While IoT devices enhance operational efficiency, they also introduce numerous entry points for cybercriminals, expanding the potential attack surface. Cloud computing, although offering scalability and flexibility, raises concerns about data privacy and the security of third-party services. To address these multifaceted challenges, this paper explores the critical importance of cybersecurity in protecting CI. It will examine key strategies to enhance resilience against cyber threats, analyze emerging threats that could compromise CI, and provide recommendations for building a robust cybersecurity workforce capable of responding to these evolving challenges. By understanding the vulnerabilities and risks associated with critical infrastructure, stakeholders can better implement advanced cybersecurity strategiesto safeguard the systems that underpin national security and economic stability.